The morphological efforts of Muhdib al-Din al-Muhalabi In writing Alfred systems and inventory Alcheraed (Journal of the College of Basic Education, 2022)
Praise be to God, who is the most merciful of the merciful in the situation of pardon and mercy and the most severe of punishers in the situation of punishment and vengeance, and prayers and peace be upon the best of all his creation Muhammad and his good and pure family, and his honorable companions, and to proceed:The Arabic language has distinguished men who have done their utmost to preserve it and to facilitate its sciences for scholars, but there are some of them who did not reveal their efforts, and among them is Muhdhab al-Din al-Muhalabi (d. The efforts are worth considering; This is because it included the different levels of language towards it, its morphology, and its sound, and based on that, we will have a pause in this research at his morphological efforts in his book “Nazm al-Fa’ra’id” and “Encounting the Shara’id”.